Eksistensi Awik-Awik Sebagai Legalitas Pernikahan Dini di Pulau Lombok - Muhammad Yuslih (Universitas Islam Negeri Antasari Banjarmasin, 2023)
The value of local wisdom in the Sasak community on the island of Lombok has shifted away from the awik-awik tradition. This shift is believed to have contributed to the high rate of early marriage. The researcher aims to investigate whether the awik-awik tradition is the cause of early marriage practices, using Anthony Giddens' theory of legal awareness and structuration as a framework. This qualitative research employs interview and documentation methods to gather data. The study's findings suggest that the awareness of the law of 'awik-awik' among the Sasak people, particularly minors, is very low. This is supported by the number of young people who intentionally violate 'awik-awik' by getting married without their parents' permission or blessing. Furthermore, there is a close relationship between the perpetrators of early marriage (agents) and the structure of this violation of 'awik-awik'. Agents are under the authority of community and religious leaders, such as the dusun head, RT, and penghulu. If someone violates the awik-awik, these leaders are the first to take action. Violating the awik-awik is considered a disgrace, especially for minors, who may be forced into marriage as a result. It is important to note that minors who violate the awik-awik have no choice but to marry, as this is a legitimate sanction according to the awik-awik.